MARKUPS AND WELFARE COSTS OF BUSINESS CYCLES IN TURKEY - Yilmaz, Ensar (WILEY, 2014)
The paper, using a simple theory-based measure of the variations in aggregate economic efficiency in a New Keynessian structure, analyses the nature of the business fluctuations and estimates their welfare costs in Turkey during the period 1998-2009. The measure contains two components: a price markup and a wage markup. It seems that the latter mainly drives the fluctuations in Turkey. The paper also shows that inefficient fluctuations in the allocation of resources do generate moderate welfare costs on average. However, the aggregate efficiency costs increase much more during deep recessions.
Keywords: business cycles; countercyclical markups; welfare costs; Business & Economics